Biliary tract rhabdomyosarcoma: a report from the Soft Tissue Sarcoma Committee of the Associazione Italiana Ematologia Oncologia Pediatrica. Issue 3 (June 2018) - Perruccio, Katia; Cecinati, Valerio; Scagnellato, Angela; Provenzi, Massimo; Milano, Giuseppe Maria; Basso, Eleonora; Manzitti, Carla; Cecchetto, Giovanni; Alaggio, Rita; Di Martino, Martina; Schiavetti, Amalia; Melchionda, Fraia; et al.
Introduction: Rhabdomyosarcoma is a soft tissue malignant musculoskeletal tumor frequent in children. Biliary duct localization is extremely rare, but it is the most common cause of malignant obstructive jaundice in pediatric patients. Methods: This report describes a series of 10 patients under 18 years of age with biliary tract rhabdomyosarcoma who were enrolled, from 1979 to 2004, in 3 consecutive Italian pediatric cooperative protocols that had been drawn up by the Soft Tissue Sarcoma Committee of the Associazione Italiana Ematologia Oncologia Pediatrica (AIEOP). Results: Considering initial and delayed surgery, tumor resection was achieved in 7 cases, 3 complete with free margins (2 liver transplants) and 4 with microscopic residual disease. Chemotherapy was given to all patients and radiotherapy to 3. At present, 5 patients survive in complete remission 90-200 months after diagnosis while 4 died of disease progression or relapse and 1 of liver transplant-related complications. Conclusions: Better outcomes in this series were associated with the feasibility of conservative surgery due to the favorable location of the tumor, in particular in the common bile duct. Chemotherapy and radiotherapy might obviate the need for demolitive surgery or liver transplant, which were linked to worse outcomes in our series.